Risk Assessment Of Occupational Accidents In The Construction Industry In The Northern Region Of Peninsular Malaysia - Abdul Halim, Nur Nadia Adila (2021)
Occupational accident rates in the construction industry are among the highest compared to other industries due to the unique nature of the process involved. Thus, this industry is being considered the most hazardous sector. The first objective of this research is to determine the causes of fatalities in the Malaysian construction industry using secondary data during a period of five years (2013-2018). The second objectives of this research is to determine the perception of regulators on the factors that contribute to occupational accidents and the risk of accidents in the Malaysian construction industry. The last objective of this research is to analyze the relationship between the risk of occupational accidents and illnesses and the causes of the accidents in the Malaysian construction industry from the perspective of regulators. This research was conducted by distributing a survey questionnaire among OSH regulators in the northern region of Malaysia. A total of 130 responses were received from respondents. From the analysis, falling from elevation (43%) recorded the highest number of accident cases followed by struck-by (34%) and the main accident causes were management elements (58 cases) followed by worksite and human elements with 57 cases and 30 cases respectively. Fall from elevation (R2= 0.214; T= 5.600; P = 0.000) and fall at same level (R2= 0.150; T= 5.061; P = 0.000) has the most significant relationship with the worksite, management and external accidents causes by using Structural Equation Modelling (SEM) analysis to validate the relationship between the observed variables and latent variables as used to test the hypothesis